COMBINING ABILITY, GENE ACTION AND HETEROSIS USING CMS LINES IN HYBRID RICE (ORYZA SATIVA L.). - PRATAP, NARENDRA; SHEKHAR, RAJ; P. K. SINGH,; S. K. SONI, (The Bioscan, 2013)
Combining ability and heterosis studies for grain yield and its component traits in aromatic and non-aromatic rice. Combining ability revealed higher specific combining ability variance than their respective general combining ability variances indicating the predominance of non-additive gene effects indicated relevance of heterosis breeding for improving the yield and yield contributing attributes. Among the lines IR 58025A (1.31) and IR 79156A (0.41); among testers Narendra Usar 3 (7.16), Swarna (6.99), Usar 1 (6.37), Pankaj (4.19), Pusa Sugandha 3 (2.94) and Taraori Basmati (0.82) were emerged as good general combiners for yield along with other related components, thus these were utilize as potential donor. Among these Narendra Usar 3 showed good GCA for majority of the yield enhancing traits except L:B ratio (-0.08) and spikelet per panicle (-4.81). Out of 51 hybrids, eight hybrids were identified to exploit heterosis in positive direction with desirable SCA effects and high per se performance for yield and other traits. Among aforesaid crosses one cross “IR 79156 A × Swarna” and one cross “IR 80555 A × Pusa Sugandha 3” were found significantly desirable cross combination for heterosis breeding in non-aromatic and aromatic rice group, based on SCA performance and heterosis over better parent and standard variety for yield and its components.